Place-based motivations and normative beliefs predict pro-environmental behavior across involvement profiles. (September 2021) - Johnson, Dana N.; Shipley, Nathan J.; van Riper, Carena J.; Kyle, Gerard T.; Wallen, Kenneth E.; Landon, Adam; Absher, James
Abstract: Understanding the relationships among social psychological drivers of pro-environmental behavior has been the focus of a long-standing body of research aimed at minimizing human impacts on the environment. Within public land management contexts, empirical evidence has suggested that place-based motivations and normative beliefs explain why people intend to engage in behavior that benefits the environment; however, the personal relevance of outdoor activities varies, in that recreationists often report distinct degrees of involvement that influence patterns of thought and behavior. Therefore, we tested the moderating effect of enduring involvement in outdoor recreation on the relationships among motivations, normative beliefs, and pro-environmental behaviors that reflected tenets of the Leave No Trace (LNT) educational outreach program. We segmented respondents into involvement profiles and tested a series of hypothesized relationships using multi-group structural equation modeling. Data were derived from a study of white water rafters on the Kern Wild and Scenic River in California's Sierra Nevada. Results indicated that both the strength and influence of select motivations on normative beliefs are stronger among individuals with higher involvement in rafting. A relationship between respondents' stated levels of importance for achievement as a motive for activity participation and normative beliefs about LNT also emerged among respondents with medium levels of involvement, whereas normative beliefs about LNT are associated with place-based motives for being with similar people and being in nature among those with high levels of involvement. These results explain the relationships among multiple antecedents of behavior within the context of a high-risk wilderness experience. Management implications: The behavioral phenomena examined in this research explain the development of stewardship practices to help sustain environments while optimizing visitor experiences in the outdoors.Natural resource recreation managers should consider the personal relevance of activities as defining features that explain variation in motivations and responses to normative pressure. The presented results indicate that framing information in line with the involvement profiles will be more likely to resonate with recreationists in related contexts. Respondents were motivated to engage in white water rafting to be around similar people, enjoy nature, learn, and escape from personal and social pressures, but these motivations vary in accordance with levels of involvement. In settings where recreationists are presented with opportunities to engage in nature-based recreation that requires specialized skills, those with high levels of involvement may be more sensitive to normative pressures to protect the expected outcomes of their nature-based goals and desire to be around other highly involved recreationists. Highlights: We examined relationships among behavioral phenomena across levels of involvement. Select motivations increase as does involvement in high risk recreation. Achievement is important for respondents with medium levels of involvement. Similar people and nature are most important for respondents with high involvement. Results guide efforts to instill environmental ethics in outdoor recreationists.